Why is there controversy regarding China’s staple grain food market integration? Evidence and implication from price convergent club analysis - Zhu, Y.; Ren, X.; Oxley, Leslie; Ma, H. (2015)
© 2015 Taylor & Francis. There remains ongoing controversy regarding the degree to which Chinese food markets are integrated. Some economists conclude that China’s grain economy is well integrated, while others argue that China’s gradual reforms have led to fragmented domestic markets while others conclude that previous studies have produced mixed results. To reconcile the debate, this article models and analyses the behaviour of China’s food grain retail markets by testing for the existence of the convergent price clustering clubs using appropriate econometric methods and price data over 1997–2010. The article finds evidence as to why the controversy remains by identifying a number of small divergent price clustering clubs where it is hard to conclude that China’s food grain markets are fully integrated. However, given that large convergent clustering clubs were also identified, it can be concluded that the degree to which Chinese grain food retail markets are integrated is ‘high’. This finding is important for those who plan to investigate the economic behaviour of grain production under the assumption of a pure, fully integrated, food market economy in China.